PENGARUH VARIASI JUMLAH NOZZLE TERHADAP DAYA LISTRIK YANG DIHASILKAN PADA PROTOTYPE TURBIN PELTON - Assauri, Sufyan; Margianto, Margianto; Marlina, Ena (UNIVERSITAS ISLAM MALANG, 2016)
Water energy is one renewable energy that are now widely developed in Indonesia to meet the needs of electrical energy increases, estimated in 2020 the electric energy needs of Indonesia increased rapidly up to three times. In addition, the power plant used in Indonesia to meet its electrical energy needs, mostly mesar a fossil-fueled power plants, such as oil, natural gas, and coal. Reserve source of energy derived from fossil expected to last 40 years for petroleum, 60 years for natural gas, and 200 years for coal, the limitations amid the increasing demand for electricity and the demands to tackle environmental pollution to be a challenge for Indonesia to develop energy sources are renewable, such as nuclear power, wind, water, solar, geothermal, and bio-energy. Water energy harnessed through the potential energy of water into mechanical energy weeks to turn a turbine and then converted into electricity by a generator. By varying the use of the number of nozzles used is 1 nozzle, two nozzle, 3 to determine how much influence ? , 90 ? , 60 ? nozzle and valve openings 30 the reactor nozzle consumption amount of electricity generated in this pelton turbine prototype. The highest electric power generated in the use of 3 nozzle valve openings produce 0.00072 m3 / s flow rate, 91.71 m / s flow rate, ? invitation 90 411 rpm rotation pulleys runner, and the electric power generated by 10.5357 watts. Can be deduced that the number of nozzle use can meningkatkat electric power generated petlton turbine prototype.